2021
DOI: 10.1007/s10067-021-05743-2
|View full text |Cite
|
Sign up to set email alerts
|

Disease-modifying anti-rheumatic drugs for the management of Takayasu arteritis—a systematic review and meta-analysis

Abstract: The pharmacotherapy of Takayasu arteritis (TAK) with disease-modifying anti-rheumatic drugs (DMARDs) is an evolving area. A systematic review of Scopus, Web of Science, Pubmed Central, clinical trial databases and recent international rheumatology conferences for interventional and observational studies reporting the effectiveness of DMARDs in TAK identified four randomized controlled trials (RCTs, with another longer-term follow-up of one RCT) and 63 observational studies. The identified trials had some conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 109 publications
0
71
0
Order By: Relevance
“… 47 , 48 Based on observational studies, anti-tumor necrosis factor-alpha (anti-TNF) agents and tocilizumab achieve clinical response in nearly three-fourth patients, although their effect on angiographic stabilization is less defined. 49 Sub-optimal angiographic response with currently used immunosuppressive therapies in TAK lends credence to the hypothesis that adding an anti-fibrotic therapy to immunosuppressive therapy might favorably modulate vascular remodeling by reducing fibrosis consequent to inflammation-associated vascular injury. Costly biological therapies are inaccessible in vast swathes of the globe including India.…”
Section: Discussionmentioning
confidence: 97%
“… 47 , 48 Based on observational studies, anti-tumor necrosis factor-alpha (anti-TNF) agents and tocilizumab achieve clinical response in nearly three-fourth patients, although their effect on angiographic stabilization is less defined. 49 Sub-optimal angiographic response with currently used immunosuppressive therapies in TAK lends credence to the hypothesis that adding an anti-fibrotic therapy to immunosuppressive therapy might favorably modulate vascular remodeling by reducing fibrosis consequent to inflammation-associated vascular injury. Costly biological therapies are inaccessible in vast swathes of the globe including India.…”
Section: Discussionmentioning
confidence: 97%
“…Cohort studies have showed that methotrexate ( 45 ), azathioprine ( 46 ), mycophenolate mofetil ( 47 ), leflunomide ( 48 ) and cyclophosphamide ( 49 ) could improve clinical and radiological manifestations of TAK and have a GC-sparing effect. However, there are no randomized trials comparing the efficacy of different csDMARDs, and two recent meta-analysis on csDMARDs in TAK indicated similar efficacy rates between these drugs ( 25 , 50 ). Therefore, clinical practice typically reflects the results of these low level of evidence data and expert opinion.…”
Section: Takayasu Arteritis: Conventional Dmardsmentioning
confidence: 99%
“…A recent meta-analysis by Misra et al ( 25 ) analyzed 19 observational studies on TNFi in TAK, showing that more than 80% of treated patients attained at least partial clinical response, angiographic stabilization, improvement in PET-CT and normalization of inflammatory markers. Relapse rate was estimated as 32% but with considerable heterogeneity across studies.…”
Section: Takayasu Arteritis: New Targeted Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies reporting PROMs in TAK (both adultonset [18][19][20][21] and childhood-onset [22] forms) reporting original data on any PROM were included. Due to the paucity of randomized controlled trials (RCTs) in TAK [23], both RCTs and observational studies (with or without control group) were included. Review articles, case reports, editorials and letters to editors were excluded.…”
Section: Study Selectionmentioning
confidence: 99%